2004
DOI: 10.1080/10739680490266216
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein IIB/IIIA‐Inhibition and Microcirculatory Alterations During Experimental Endotoxemia—An Intravital Microscopic Study in the Rat

Abstract: GP IIb/IIIa inhibition, using abciximab, protects against endothelial dysfunction and an increase in leukocyte adherence to the vascular wall during experimental endotoxemia. The protective properties of abciximab on microcirculation seemed to be leukocyte-independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 50 publications
(77 reference statements)
1
25
0
Order By: Relevance
“…Otherwise, no additional risk of infection has been associated with abciximab (Reopro package insert). In fact, there is in vitro and murine model evidence that glycoprotein IIb/IIIa inhibition protects against endothelial cell dysfunction and leukocyte adherence to the vascular wall during experimental endotoxemia (88,190).…”
Section: Monoclonal Antibodies For Cardiovascular Diseasementioning
confidence: 99%
“…Otherwise, no additional risk of infection has been associated with abciximab (Reopro package insert). In fact, there is in vitro and murine model evidence that glycoprotein IIb/IIIa inhibition protects against endothelial cell dysfunction and leukocyte adherence to the vascular wall during experimental endotoxemia (88,190).…”
Section: Monoclonal Antibodies For Cardiovascular Diseasementioning
confidence: 99%
“…In addition, intravital microscopy has also been used to test novel prophylactic and therapeutic approaches that aim to prevent or attenuate manifestations of sepsis-associated microvascular disorders and cellular dysfunctions. In the mesentery, microcirculatory observations have focused on capillary obstruction, capillary or arteriolar density, microvessel reactivity and leukocyte-endothelial interactions in post-capillary venules (Harris, 2006;Kim & Harris, 2006;Nakagawa et al, 2006Nakagawa et al, , 2007Schimidt et al, 1997;Smalley et al, 2000;Walther et al, 2004;Woodman et al, 2000). A representative photomicrograph of rat mesenteric microcirculation is shown in Figure 3.…”
Section: Intravital Microscopy In the Assessment Of Microcirculationmentioning
confidence: 99%
“…Microcirculatory dysfunctions, as seen in humans (De Backer & Dubois, 2001;De Backer et al, 2002;Groner et al, 1999;Trzeciak et al, 2007), have been shown to occur in most experimental models of sepsis (Baveja et al, 2002;Kamoun et al, 2005;Kim & Harris, 2006;Kubo et al, 1999;Nakagawa et al, 2006Nakagawa et al, , 2007Nakajima et al, 2001;Schimidt et al, 1997;Smalley et al, 2000;Waisman et al, 2006;Walther et al, 2004;Woodman et al, 2000). Endotoxin infusion is a widely used experimental model (Kim & Harris, 2006;Schimidt et al, 1997;Smalley et al, 2000;Nakajima et al, 2001).…”
Section: Intravital Microscopy In the Assessment Of Microcirculationmentioning
confidence: 99%
See 1 more Smart Citation
“…We know from the literature that endothelial damage during early endotoxemia is leukocyte-independent and can be inhibited by glycoprotein IIb/IIIa receptor antagonism and by nitric oxide [4,5].…”
Section: Introductionmentioning
confidence: 99%